2001
DOI: 10.1538/expanim.50.441
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Preservation of Mouse Oocytes at 5.DEG.C..

Abstract: Abstract:The temporary preservation of oocytes without freezing would be useful for some experiments. ICR mouse oocytes were kept in a preservation medium under mineral oil for 1, 2, 3, 4 or 7 days at 5°C, and 1 or 2 days at 37°C. In vitro fertilization was attempted on oocytes rinsed with TYH medium after preservation. More than 70% of morphologically normal oocytes were recovered from each preservation group. Fertilization rates of oocytes preserved for 1, 2, 3, 4 or 7 days at 5°C were 69.9, 66.5, 45.3, 26.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…On the other hand, when oocytes were stored at 37 C in an incubator, 64 to 83% of oocytes were externally normal, but none developed to the morula/blastocyst stage after parthenogenetic activation. Tsuchiya et al [21] reported that, when oocytes were stored at 5C for one day, 79% of stored oocytes were normal and 30% of stored oocytes developed to the morula/ blastocyst stages after in vitro fertilization. However, they did not specifically categorize the oocytes by gross morphology as we did; therefore, their designation of "normal" may differ certainly from ours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, when oocytes were stored at 37 C in an incubator, 64 to 83% of oocytes were externally normal, but none developed to the morula/blastocyst stage after parthenogenetic activation. Tsuchiya et al [21] reported that, when oocytes were stored at 5C for one day, 79% of stored oocytes were normal and 30% of stored oocytes developed to the morula/ blastocyst stages after in vitro fertilization. However, they did not specifically categorize the oocytes by gross morphology as we did; therefore, their designation of "normal" may differ certainly from ours.…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, only a few investigations of room temperature storage of oocytes have been conducted [21] and none have succeeded in producing viable offspring from such aged oocytes in vitro. In the present study, we demonstrate that alt hou gh m ost in v i tro a g e d o o c y t e s h av e irreversible damage to the metaphase-II spindle, at least some retained full developmental potential after storage for one day at room temperature.…”
mentioning
confidence: 99%
“…In several species, including rabbits (17), cows (18,19), sheep (20) and mice (21)(22)(23)(24)(25)(26)(27)(28)(29), successful refrigeration of preimplantation embryos at 0-7 C has been reported. Although short-term storage of unfertilized oocytes is not a common practice, there have been many studies on the refrigeration of fertilized oocytes in several mouse strains (5,22,26).…”
Section: Discussionmentioning
confidence: 99%
“…1971); the osmolality of the medium is 290 ± 10 mOsm. Standard TYH medium for IVF is usually supplemented with 5.5 m m glucose during pre‐incubation and insemination (Tsuchiya et al. 2001).…”
Section: Medium Preparationmentioning
confidence: 99%